The Accuracy Bound for Positioning the 5R Planar Parallel Manipulator Subjected to Uncertainties in Dimensions and Actuations - Adriyan Adriyan; Asmara Yanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
This article is aimed to determine the accuracy bound for positioning the 5R planar parallel manipulator under the uncertainties in its dimensions and actuation. The accuracy bound is investigated numerically using the interval analysis and multi-dimensional bisection method (MDBM). These numerical methods can give multiple solutions within the workspace of the manipulator. Then, the exact solution is utilized for comparison with the numerical solutions. It is shown that the interval analysis via the interval Newton method gives the guaranteed bounds for positioning accuracy. Meanwhile, the MDBM and the exact solution coupling with the Monte Carlo simulation produce a scattered random value in a parallelogram shape inside the solution yielded by the interval Newton method. Overall, those three methods give nearly a good agreement in terms of that accuracy, but they are different at computation time.